Inner Loop-Based Robust Control Design Considering Uncertain Grid Impedance for a Single-Phase AC–DC Converter - Sokvan In; Chivon Choeung; Sokna San; Socheat Yay; Seven Siren; Channareth Srun (Control Systems and Optimization Letters, 2026)
Single-phase AC–DC converters based on an H-bridge active rectifier topology are widely used in applications such as electric vehicle charging and renewable energy interfaces. To achieve zero steady-state error using integral control, it is essential to regulate the output in the dq-synchronous frame. A key challenge in controlling single-phase power converters is the inability to directly convert single-phase signals to dq-frame signals. This paper proposes the use of a digital all-pass filter to generate β-signals, which provide the orthogonal component required for dq-transformation in single-phase systems. The control strategy involves an outer loop proportional–integral (PI) controller for regulating the output DC voltage, while an inner loop a linear matrix inequality (LMI)-based robust state-feedback controller with integral action is employed to regulate the AC current. The dq-frame transformation enables effective current regulation, while the robust control law ensures closed-loop stability based on Lyapunov function in the presence of parameter uncertainties. The robustness of this control approach is demonstrated by considering system uncertainties, including variations in the filter inductance with nominal value 3 mH, and the effectiveness of the proposed control is confirmed through simulation results under different resistive load conditions, demonstrating stable operation and accurate DC voltage regulation. Future work will focus on experimental validation of the proposed control strategy and investigation of converter performance under grid disturbance conditions such as voltage unbalance and harmonic distortion.